Expression of a variant surface glycoprotein of Trypanosoma gambiense in procyclic forms of Trypanosoma brucei shows that the cell type dictates the nature of the glycosylphosphatidylinositol membrane anchor attached to the glycoprotein - Paturiaux-Hanocq, F; Zitzmann, N; Hanocq-Quertier, J; Vanhamme, L; Rolin, S; Geuskens, M; Ferguson, M; Pays, E (Portland Press, 1997)
Procyclic forms of Trypanosoma brucei have been genetically modified to express the major metacyclic variant surface glycoprotein (VSG variant AnTat 11.17) of Trypanosoma gambiense. The VSG is expressed in an intact membrane-bound form that can be detected over the entire plasma membrane, together with procyclin, and as a series of lower-molecular-mass fragments that are mostly soluble degradation products. The presence of degraded VSG in the cells and the culture medium suggests that VSG is not efficiently processed and/or efficiently folded when expressed in procyclic cells. The level of procyclin expressed on the surface of these cells is slightly reduced, although there is no difference in procyclin mRNA levels. The intact membrane-bound form of the VSG is N-glycosylated with oligomannose structures and contains a glycosylphosphatidylinositol (GPI) membrane anchor that can be biosynthetically labelled with [3H]ethanolamine. The anchor is sensitive to mammalian GPI-specific phospholipase D but, like the anchor of procyclin, it is resistant to the action of bacterial phosphatidylinositol-specific phospholipase C. This pattern of phospholipase sensitivity suggests that the GPI anchor acquired by VSG when expressed in procyclics is acylated on the inositol ring and therefore resembles a procyclic procyclin-type anchor rather than a trypomastigote VSG-type anchor with respect to the lipid structure. The VSG expressed in procyclics was sensitive to the action of a mixture of sialidase, beta-galactosidase and beta-hexosaminidase, suggesting that the VSG GPI anchor also contains a sialylated polylactosamine side-chain modification similar to that described for procyclin. These results indicate that the nature of the protein expressed has little influence on the post-translational modifications performed in the secretory pathway of procyclic trypanosomes.